2001
DOI: 10.1128/iai.69.8.4816-4822.2001
|View full text |Cite
|
Sign up to set email alerts
|

Protection of BALB/c Mice againstBrucella abortus544 Challenge by Vaccination with Bacterioferritin or P39 Recombinant Proteins with CpG Oligodeoxynucleotides as Adjuvant

Abstract: The P39 and the bacterioferrin (BFR) antigens of Brucella melitensis 16M were previously identified as T dominant antigens able to induce both delayed-type hypersensivity in sensitized guinea pigs and in vitro gamma interferon (IFN-␥) production by peripheral blood mononuclear cells from infected cattle. Here, we analyzed the potential for these antigens to function as a subunitary vaccine against Brucella abortus infection in BALB/c mice, and we characterized the humoral and cellular immune responses induced.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 56 publications
2
78
1
2
Order By: Relevance
“…The significant rise (P B0.001) in the titre of IgG in mice of group 1 compared to group 2 and 3 supports the effect of adjuvant (CpG ODN). Our results are in agreement with the previous report of Klinman et al (2004) and Al-Mariri et al (2001). The mice immunised with rOMP28'CpG showed relative predominance of IgG2a over IgG1, however, IgG1 was relatively predominant in rOMP28 immunised mice.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The significant rise (P B0.001) in the titre of IgG in mice of group 1 compared to group 2 and 3 supports the effect of adjuvant (CpG ODN). Our results are in agreement with the previous report of Klinman et al (2004) and Al-Mariri et al (2001). The mice immunised with rOMP28'CpG showed relative predominance of IgG2a over IgG1, however, IgG1 was relatively predominant in rOMP28 immunised mice.…”
Section: Resultssupporting
confidence: 83%
“…This suggested the role of CpG ODN in antigen-specific isotype class switching, when coadministered with rOMP28 and induction of Th1 arm of immune response (Figure 1B and C). This corroborated to the finding of Al-Mariri et al (2001) and Klinman et al (1999).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…utilizing numerous proteins (2,12,15,25,36). Most of the studies have shown satisfying results in animal models but no clear prospect for further experimentation in humans.…”
Section: Discussionmentioning
confidence: 99%
“…For challenging purpose, B.melitensis 16 M was used (obtained from vet. Sera vacci Rec Institute, Cairo, Egypt) and was cultured under optimal conditions in tryptose soya agar supplemented with yeast extract 10 g/ lml (Oxoid, England) incubated overnight at 37°C for 72 hrs in 5% Co 2 to ensure sufficient cell density (10). The obtained bacteria were harvested and suspended in PBS and the abundance was adjusted to be 1x10 5 CFU/200µl for protection experiment.…”
Section: Materials and Methods:-mentioning
confidence: 99%